A pilot study of power doppler sonography using tumour vascularity pattern in differentiating benign from malignant breast lesion - Said, Siti Nor Badriati Sheik (2006)
Objective: 1. To determine the specificity and sensitivity of the criterias of the tumour vascularity pattern using power Doppler sonography in differentiating benign and malignant breast lesion. 2. To find any association between tumour vascularity pattern and size of benign and malignant breast lesion Methods and Materials: Ethics committee approval and informed consent were obtained. This study was carried out in Hospital USM, Kubang Kerian, Kelantan for 16 months from July 2004 until October 2005. Power Doppler sonography using 13.5MHz transducer was prospectively performed on a total of 40 patients with breast lesion. The tumour vascularity criterias assessed were the flow, distribution, vessel morphology and presence of penetrating artery. FNAC (Fine needle aspiration cytology) and/or HPE (Histopathological examination) were done for all cases. The power Doppler criterias and HPE were analysed using univariate analysis. The sensitivity, specificity, positive predictive value and negative predictive value calculated using diagnostic table. Result: There was detectable blood flow in 13 infiltrating ductal CA and 16 benign lesions. The mean size of vascular lesion was 30.5mm with 1.8mm standard deviation. The size of the lesions may have played a part in the vascularity of the lesion with a p value of 0.005 for flow characteristics. In the vascular lesions, irregular vessel and presence of penetrating artery showed a significant p value of 0.004 and 0.0 11. There was no single vascularity pattern which was specific for benign and malignant breast lesion. The descriptors of vessel morphology, flow, distribution and penetrating artery were not found to be highly predictive of malignancy with positive predictive value of 50. 0%, 54.5%, 56.0% and 63.1% respectively. High negative predictive values were interestingly noted in the following descriptors: peripheral distribution (100%), low flow (88.9%) and regular vessel (87.5%). Conclusion: Power Doppler US provided only limited additional information in differentiating benign solid breast lesions from malignant lesions. Vascular assessment was helpful only when it supported a benign morphology.